The Impact of Religious Coping on Quality of Life Among Hemodialysis Patients: A Cross-Sectional Study - Safruddin Safruddin; Sumbara Sumbara; Wini Resna Novianti; Junaidin Junaidin; Santi Puspitasari; Rahmat Hidayat (PT.Mantaya Idea Batara, 2026)
Background: Patients with End-Stage Renal Disease (ESRD) require routinehemodialysis. Long-term hemodialysis often leads to physical, psychological, and socioeconomic challenges that reduce quality of life. Religious and spiritual coping mechanisms represent important adaptive strategies for managing chronic illness and improving well- being. This study investigates the relationship between religious coping strategies and quality of life in patients with ESRD undergoing hemodialysis. Methods: An analytic observational study with a cross-sectional design was conducted involving 80 patients receiving hemodialysis therapy. Participants were recruited through accidental sampling. Data were analyzed using descriptive statistics and Spearman correlation tests to assess the relationship between religious coping and quality of life across four domains:physical, psychological, social, and environmental. Result: The results indicated that patients employing positive religious coping experienced significantly better quality of life across all domains (p < 0.005). Conversely, patients using negative religious coping demonstrated lower quality of life in these domains (p < 0.005). Conclusion: These findings emphasize that religious coping functions as a psychosocial resource for patients undergoing hemodialysis. Incorporating coaching interventions grounded in religious coping into nursing care may enhance patients' quality of life with End-Stage Renal Disease(ESRD).